Strategies for Utilising Educational Technology to Improve the Competitiveness of Student Small Businesses - Sutrisno Sutrisno (Lembaga Intelektual Muda (LIM) Maluku, 2023)
In the era of globalisation and advances in information technology, competition in various business sectors is increasingly fierce, including in the world of small businesses. On the other hand, higher education also faces the challenge of preparing students to become graduates who have high competitiveness in the ever-changing labour market. The purpose of this study is to explain the strategy of utilising educational technology to improve the competitiveness of students' small businesses. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that the integration of educational technology has a significant positive impact on the growth of small businesses as well as students' readiness to face competition in the global market. Through technology-based education, students are given the opportunity to deepen their knowledge of business aspects, develop relevant technological skills, and design smarter strategies. Technology adoption supports operational efficiency with automation of routine tasks, more accurate inventory management, and better financial management. The utilisation of technology also provides opportunities for innovation in products, services, and business processes, which in turn helps small businesses to compete better in the marketplace.